Selection of Cricket players using analytical hierarchy process - Kamble, A. G.; Venkata Rao, R.; Kale, A.V.; Samant, S.P. (International Journal of Sports Science and Engineering, 2011)
Cricket team needs to be more flexible, balanced and diversified. Each player has his/her own characteristics. In choosing the right player, there is not always a single definite attribute for selection. Selectors have to take into account a number of attributes. Optimality of the team changes with the change in different attributes for selecting the optimal team players. This paper, presents a cricket team players selection procedure from a set six level players in complex situations using analytic hierarchy process. The proposed method helps to evaluate and ranks the players. One example is included to illustrate the approach.